Data Transmission Issues in Business while using CC – A Survey - Fairosebanu, A; A. NishaJebaseeli, A (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is a huge storage domain by which everyone can access the functions and utilities through the Internet, irrespective of the locations without any difficulties in maintenance and management. Security is a vital aspect in any business to sustain in the digitalized world forever. Cloud computing also enhances in the transfer of data without any deviations. The major security issues like breaches, inadequate access management, specter and meltdown, loss and DOS attacks of all business oriented data